2018
DOI: 10.1111/tpj.14096
|View full text |Cite
|
Sign up to set email alerts
|

Wheat grain protein accumulation and polymerization mechanisms driven by nitrogen fertilization

Abstract: In wheat (Triticum aestivum) grain yield and grain protein content are negatively correlated, making the simultaneous increase of the two traits challenging. Apart from genetic approaches, modification of nitrogen fertilization offers a feasible option to achieve this aim. In this study, a range of traits related to nitrogen-use efficiency in six Australian bread wheat varieties were investigated under different nitrogen treatments using 3-year multisite field trials. Changes in the individual storage protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 47 publications
5
41
0
Order By: Relevance
“…Sabine, Oberfoster, Werteker, Grausgruber, and Lelly (1997) reported that the Glu-B1 alleles 7 + 9 and the Glu-D1 alleles 5 + 10 occurred more frequently in cultivars with better bread-making quality, and no cultivar with good quality contained subunits 6 + 8 and 2 + 12. Yu et al (2018) reported that grain protein content was more sensitive to N application than grain yield and that protein content was mainly determined by genotype. Moreover, SST806 is the commercial standard for spring wheat baking quality in South Africa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sabine, Oberfoster, Werteker, Grausgruber, and Lelly (1997) reported that the Glu-B1 alleles 7 + 9 and the Glu-D1 alleles 5 + 10 occurred more frequently in cultivars with better bread-making quality, and no cultivar with good quality contained subunits 6 + 8 and 2 + 12. Yu et al (2018) reported that grain protein content was more sensitive to N application than grain yield and that protein content was mainly determined by genotype. Moreover, SST806 is the commercial standard for spring wheat baking quality in South Africa.…”
Section: Resultsmentioning
confidence: 99%
“…Both can be improved through N fertilization strategies, such as the rates and timing of N fertilization Zhong et al, 2019). Yu et al (2018) reported that grain protein content was more sensitive to N application than grain yield and that protein content was mainly determined by genotype.…”
Section: Resultsmentioning
confidence: 99%
“…Although the accumulation of polymeric proteins starts as early as 7 d post-anthesis and lasts during the entire period of grain development, the accumulation of UPP fraction only begins at the later stage of grain development (from 30 to 45 d post-anthesis). Yu et al [102] found that UPP formation involves peptidyl-prolyl cis-trans isomerase (PPIase) SUMOylation with the assistance of small ubiquitin-related modifier 1 and that high nitrogen availability facilitates this connection. Additionally, luminal binding protein 2 in the endoplasmic reticulum has a similar function to PPIase in the aggregation of protein.…”
Section: Core Factors Affecting Dough Storage Protein Composition Andmentioning
confidence: 99%
“…Small ubiquitin-related modifier 1 (SUMO1) is involved in the transport of proteins from the nucleus to the cytoplasm, and it contributes to the stability of proteins [20]. PPIase and SUMO1 interact to facilitate the formation of protein polymers [21]. Protein disulfide isomerase (PDI) catalyzes the formation of disulfide bonds, which are regarded as the determinant bridges during protein polymerization [22].…”
Section: Introductionmentioning
confidence: 99%
“…Protein disulfide isomerase (PDI) catalyzes the formation of disulfide bonds, which are regarded as the determinant bridges during protein polymerization [22]. The high level expression of genes encoding PPIase, SUMO1, and PDI enhances the folding of storage proteins during grain-filling, thereby leading to the accumulation of more glutenin macropolymers (GMPs) [11,21,23]. HMW-GSs contribute to glutenin polymerization via intra-/intermolecular disulfide bonds and hydrogen bonds [4], and the effects of single HMW-GSs on glutenin polymerization have been reported [8].…”
Section: Introductionmentioning
confidence: 99%